Linux logical volume manager. (Manning Publications, 2022)
In this course on the Linux Logical Volume Manager you'll learn: Exactly what LVM is and when to use it. How LVM creates layers of abstraction between storage devices and file systems and how to use that to your maximum benefit. The details of how to create and manage Physical Volumes, Volume Groups, and Logical Volumes. How easy it is to extend file systems while keeping the existing data online and completely accessible during the entire process. How to create mirrored logical volumes to protect your data against single points of failure. How to migrate data from one storage device to another, without taking any downtime whatsoever. And more... This course is perfect for anyone who wants to quickly get up to speed on the Linux Logical Volume Manager. It also includes a 14-page LVM Workbook that contains all the examples and commands demonstrated in the course. You can use it as your personal LVM cheat sheet.